MOTIVATION OF FARMERSMAINTAIN Tilapia TOBUSINESS IN BENGKULU SELATAN DISTRICT - Feti Purnama Syari; Irnad Irnad; Gita Mulyasari (Journal of Agri Socio Economics and Business, 2022)
Aquaculture is one of the most profitable businesses for the community economically. South  Bengkulu Regency has great potential in meeting the demand for tilapia in themarket. However, in 2018 there was a reduction in water discharge, damage to irrigation channels that began to rot or age. Based on the existing problems, the motivation of farmers who cultivate tilapia business is  reduced. The purpose of the study: 1. to analyze the motivation of farmers to maintain tilapia farming, 2. What factors influence the  motivation of  farmers to  maintain tilapia farming in South Bengkulu Regency. This study uses two types of data analysis, namely the first Likert analysis and SEM analysis. The results of this study indicate that: 1. The motivation of Tilapia fish farmers can be said to be very high motivation in maintaining their farming. 2. There are two influencing factors, namely factors that directly affect the availability of  production facilities (X1), Government support (X2),  Environmental Inputs  (X3),  Family  Head Resource Inputs (X4), Management (X5 ).) and Output (X6), while the factors that do not directly affect the Availability of Production Means (X1) affect Government Support (X2) in shaping Farmer's Motivation (Y) and the Input of Family Head Resources (X4) affects Output ( X6) in shaping the motivation of farmers (Y).